Collagenous Gastritis: An Unusual Presentation With Tubular Shaped Stomach. (July 2020) - Cortez, Nathaly; Berzosa, Manuel; Jacobs, Adam; Bloom, Michael
Collagenous gastritis is a rare histopathologic entity that causes marked subepithelial collagen deposition in the gastric mucosa. Clinical presentation is diverse, considering only less than 100 cases have been reported. However, we report a unique case of isolated collagenous gastritis in a 71-year-old female who presented with a 6-month history of dyspepsia and 27 kg weight loss. Her endoscopic findings revealed a tubular shaped stomach with diffuse gastric mucosal atrophy, findings that differ with previous case reports of a cobblestone pattern. Treatment remains unclear.